Some issues about legal regulation regarding handling dangerous goods in maritime traffic - Rukavina, Biserka (Array, 2020)
This paper analyses Ordinance on handling dangerous goods, the conditions and method of transport in maritime traffic, loading and unloading of dangerous goods, bulk and other cargo in ports and the method of preventing the spreading of oil spills in ports especially in the segment of the definition of dangerous goods, the supporting documents accompanying the handling of dangerous goods as well as supervision of the application of protective and safety measures. The author also discusses the terminological inconsistencies of important conceptual definitions while highlighting possible solutions. The paper also researches the role of the professional service, i.e., the qualified person who supervises handling dangerous goods in ports and who as such, is considered as the responsible person. The possible duality of the legal regulation of handling dangerous goods with regard to the Act on Transport of Dangerous Goods is also being researched. The last part highlights the contribution of the European Maritime Safety Agency (EMSA) and the achievements of the Republic of Croatia in establishing a system for the exchange of data on dangerous goods. In conclusion, the author gives an assessment of the compliance of the Croatian legal norm on the handling dangerous goods with international and EU solutions and makes appropriate proposals.